HUBUNGAN PENGETAHUAN IBU DENGAN KEJADIAN STUNTING BALITA DI PUSKESMAS LOA IPUH TENGGARONG - Rini Ernawati; Phenty Phenty; Ismansyah Ismansyah (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
WHO states that stunting is a nutritional or nutritional problem that commonly occurs in all children, especially in the world now, in 2017 (22.2%) or around 150.8 million children under five worldwide experienced stunting, in this condition it is necessary to attention so that stunting can be reduced. In this study, the aim was to determine the relationship between maternal knowledge about nutrition and stunting among children under 5 in the Loa Ipuh Health Center Tenggarong area. This study uses descriptive research using quantitative methods with cross sectional design. The sample of this research is mothers who have children (0-5 years) who attend the posyandu event, with a total sample of 175 respondents. The instrument used a questionnaire, data analysis by chi square test from the chi square test results obtained p value = 0.03, this means that p<(0.05) Ho is rejected, there is a relationship between mother’s knowledge about nutrition and the incidence of stunting children under five in Loa Ipuh Tenggarong Publict Health Center. It is hoped that mothers can increase knowledge about children nutrition so that they can prevent stunting in future generations.